2016
DOI: 10.15171/jcs.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Designed Respiratory Care Program on the Incidence of Ventilator-Associated Pneumonia: A Clinical Trial

Abstract: Introduction: Ventilator-associated pneumonia is a common complication of mechanical ventilation. This study aimed to evaluate the effect of designed respiratory care program on incidence of ventilator-associated pneumonia (VAP) in the mechanically ventilated patient. Methods: In this clinical trial, 64 patients were selected among those who had undergone mechanical ventilation in the ICU of Al‑Zahra Hospital, Isfahan, Iran, using convenience sampling method. The subjects were randomly allocated to interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…22 There is no consensus in the literature about the level of pressure to be maintained in the cuff, but the mean pressure should be 25 cmH 2 O. 14,17,23 Endotracheal tubes have high pressure and low volume cuff, being the pressure of the cuff essential in tube handling. 24 As changing positions during nursing care can modify this pressure, it should be measured after changing patient's position and adjusted to the recommended limits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 There is no consensus in the literature about the level of pressure to be maintained in the cuff, but the mean pressure should be 25 cmH 2 O. 14,17,23 Endotracheal tubes have high pressure and low volume cuff, being the pressure of the cuff essential in tube handling. 24 As changing positions during nursing care can modify this pressure, it should be measured after changing patient's position and adjusted to the recommended limits.…”
Section: Discussionmentioning
confidence: 99%
“…Related care to bronchial aspiration prevention Keep the headboard elevated between 30 and 45°1 [7][8][9][10][11][12][13][14][15][16][17][18][19] IIb, VI…”
Section: Endotracheal Tube Carementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding physical assessment of respiratory tract, the present study revealed that majority of ICU nurses did not perform inspection, percussion and auscultation. While after exposure to module the highest majority of nurses performed all assessment appropriately.in this regards Abbasinia et al, [22] conducted a study about the effect of a designed respiratory care program on the incidence of ventilator associated pneumonia, and concluded that a designed upper respiratory cares program can reduce the incidence of VAP.…”
Section: Practice Of Icu Nurse's For Vap Prevention Measuresmentioning
confidence: 99%
“…It occurs frequently in hospitalized patients admitted to intensive care units and submitted to mechanical ventilation. It can be classified as early when occurring up to the fourth day of intubation and as late when occurring after the fifth day (1) .…”
Section: Introductionmentioning
confidence: 99%